Perancangan Pusat Kebugaran Jasmani Anak di Surabaya - Hardjawikarta, Jovita (Intra, 2014)
This design project is a physical fitness center (Sport Centre) for the kids to play and explore methods together. The background of this idea is that children can get a complete and perfect Â education, not only intellectually increase in intelligence but also can develop in the temporal field that can help children to be more confident and can have a healthy lifestyle since the early age. The theme for designing this place is âGarden